Espectroscopia por transformada de Fourier como método de triagem na avaliação da crioscopia de leite - Erika Lopes Duarte (2018)
The milk freezing point is correlated with the soluble components and can be an indicator of fraudulent addition of water. The objective of this study was to investigate the interference of milk fat content upon the freezing point obtained by Fourier-transform infrared (FTIR), and to evaluate the relationship among freezing point, milk components, and somatic cell count (SCC). A fraction of raw milk was skimmed, obtaining cream and skim milk. Whole and skim milk were added with water (0, 2, 5, 10, 15, and 20%; experiment 1). The remaining skim milk was added with cream (5, 10, 15, 20%) and water (0, 2, 5, 10, 15, and 20%; experiment 2). Samples were analyzed for freezing point (thermistor cryoscope) and freezing point and composition (CombiScope FTIR, Delta Instruments). Additionally, 4,000 bulk tank raw milk samples with abnormal characteristics (freezing point, composition, and SCC) were screened and analyzed for adulteration (sugar, starch, salt, formaldehyde, neutralizers and hydrogen peroxide). Freezing point measured by FTIR was highly correlated with thermistor cryoscope method (above 98.5%) and, as expected, water addition was significant (P 0.001) upon increasing milk freezing point in both methods. However, high fat content in raw milk resulted in decreasing freezing point when using FTIR (P 0.001). One hundred and ninety-six samples (4.9%) were screened as suspect from a total of 4,000 bulk tank raw milk samples routinely analyzed in the laboratory. From these, 74.5% presented freezing point above 0.512°C, indicating potential fraudulent addition of water. Although sugar, starch, neutralizers or inhibitors were not found, high chloride concentrations were found in 12.2% of the samples. However, high values of SCC and freezing point were found in 7% of the samples. SCC is correlated with high chloride concentration. Most of the suspected samples presented fraudulent addition of water, which reinforces the importance of constant monitoring of the milk freezing point. Because water addition caused the inverse effect of high fat on freezing point measured by FTIR, it is important to consider the fat content of milk to avoid misinterpretation of freezing point when using FTIR method.